A ausência de um estado democrático de direito na China: uma leitura do sistema político internacional quanto a uma possível hegemonia chinesa e as relações diplomáticas sino-brasileiras desde a redemocratização do Brasil - Barros, Virgínia Coutinho de (2022)
The international system experienced a brief period of unipolarity, lived by the United States after the end of the Cold War (1947-1991). A unipolarity encompassing all hegemonic elements: political, military, economic, and technological power. Since the beginning of the 21st century, the unipolarity has been transformed into an unimultipolarity with the rise of new international actors such as the European block, China, Russia, and India, with a greater emphasis on the advance of Chinese power. In this sense, as the Chinese could achieve the development of the three hegemonic pillars that are not under their power: knowledge/technology, military and political, this paper seeks to identify whether there is a possible Chinese hegemony underway in the international political system and how Sino- Brazilian diplomatic relations have evolved since the democratization of Brazil. The general objective of this dissertation is to analyze the possibility of a possible Chinese hegemony in the world. The specific objectives are to explore the data compiled in recent years to identify whether there is a dispute between the dominance of one or more hegemonic pillars, with the inclusion of the political pillar as necessary for the conquest of hegemonic power, to address the breakdown of the division of power within these pillars encompassing the other actors of the globe, and to reaffirm the multipolar scenario structured since the beginning of the twentyfirst century. The next step is to collect the acts that have taken place between Brazil and China since 1985, dividing them by government, and to seek a historical understanding of the national scenario at the time these acts took place. Finally, the last objective is to identify the moments of greater political proximity and distance between Brazil and China. The methodological procedure adopted in this dissertation is qualitative, using as theoretical reference the authors Arrighi and Wallerstein, from the theoretical approach of the Systemic Cycles of Accumulation and the Theory of the World-System, combining the concept of hegemony structured by the author Susan Strange in four pillars of possession of hegemonic power: military, financial, production and knowledge/technology. The hypothesis addressed aims to affirm that for China, the political pillar is the most complex to be conquered, since it involves a democratization process that obtains several analytical variables and distinct results depending on its form of composition and application, besides involving Chinese society in its greater totality. In this way, the acceptance of some democratic principles would be more feasible than the loss of state power by the CCP. The result of this research is the verification that the political relationship between Brazil and China has been waning in recent years, based on the number of acts ratified by both countries, and the rise of China as an international exponent and hegemon soon. This dissertation is divided into three sections, first the decline of American hegemony and the Chinese ascension in the international system are analyzed, then the concepts of hegemony and democracy are discussed, and finally, the Sino-Brazilian relationship and the acts between both nations since the national re-democratization (1985-2022) are analyzed.